A Robust Image Watermarking Technique With an Optimal DCT-Psychovisual Threshold - Ernawan, Ferda; Kabir, M. Nomani (IEEE, 2018)
This paper presents a reliable digital watermarking technique that provides high imperceptibility and robustness for copyright protection using an optimal discrete cosine transform (DCT) psychovisual threshold. An embedding process in this watermarking technique utilizes certain frequency regions of DCT, such that insertion of watermark bits causes the least image distortion. Thus, the optimal psychovisual threshold is determined to embed the watermark in the host image for the best image quality. During the insertion of watermark bits into the certain frequencies of the image, watermark bits are not directly inserted into the frequency coefficient; rather, the certain coefficients are modified based on some rules to construct the watermarked image. The embedding frequencies are determined by using modified entropy finding large redundant areas. Furthermore, the watermark is scrambled before embedding to provide an additional security. In order to verify the proposed technique, our technique is tested under several signal processing and geometric attacks. The experimental results show that our technique achieves higher invisibility and robustness than the existing schemes. The watermark extraction produces high image quality after different types of attacks.